If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(n+9)=5+(-3)
We move all terms to the left:
3(n+9)-(5+(-3))=0
We add all the numbers together, and all the variables
3(n+9)-2=0
We multiply parentheses
3n+27-2=0
We add all the numbers together, and all the variables
3n+25=0
We move all terms containing n to the left, all other terms to the right
3n=-25
n=-25/3
n=-8+1/3
| 5c–43=c+17 | | 5.3^x=0.6^-x | | (9m+1)(4m+5)=0 | | 7(s+7)+2=9s-6 | | 5x+28=153 | | 2(p-7)-2=3p-4 | | 6(s-1)-9=2 | | ⎪2x+3⎥=7 | | 5m+180=4(12m+2) | | 2=15a-1 | | 9x+25=25+x | | 3x-(-5x)=14 | | 6*9=2(b-1) | | 6x+2=2x− | | -3+(-1)=5(v+2) | | 4n+3=n+24 | | 2(x+2)^2-10=40 | | 17(5x)=0 | | x/5=3x-14 | | 3(t-9)+4t=-3 | | 12.5+0.4e=14.75+0.25e | | 2z+8=-10z | | 12.50+0.40e=14.75+0.40e | | 2z-8=-10z | | -2z-8=-10z | | -6^2=5-13x | | 30=22+u | | (-3/5)a=12 | | r/7-4=6 | | 1/2v-1=13 | | -2(3x+4)=2/3(6+4x) | | 7q-2(2-2q)=11q-4 |